MOTIVASI, SIKAP, DAN INTENSI PENGGUNA MEDIA SOSIAL PADA KAMPANYE STOP ILLEGAL FISHING - La Moriansyah (Jurnal Manajemen & Agribisnis, 2016)
Social media is commonly used to promote social campaigns, one of which is Stop Illegal Fishing campaign. To achieve success in this campaign, some conditions have to be fulfilled i.e. positive attitudes of the social media users toward the campaigns and high intentions to provide recommendations (word of mouth) to others. This study was conducted to analyze types of motivations affecting attitudes of users towards social campaigns (stop illegal fishing) in social media. In addition, it also analyzed the influence of attitudes on users’ intentions in performing WOM. The method utilized to meet the objectives was Partial Least Square. The results showed that users’ motivation in using social media and towards the campaign messages are perceived to have significantly a positive effect on the attitude towards social campaigns in social media. Besides, the increase in the intention to perform WOM is positively influenced by the attitudes of social media users. There are differences identified in the motivation that affect the attitudes of social media users towards campaign of the two groups i.e. the social media users who have never seen the Stop Illegal Fishing campaign (151 samples) and those who have seen the campaign in social media.    Keywords:  motivation, attitude, word of mouth, user experience, uses and gratification theory, digital campaigns, social campaigns, stop illegal fishingABSTRAKMedia sosial sering digunakan untuk mempromosikan kampanye sosial, contohnya adalah  kampanye Stop Illegal Fishing. Untuk meraih kesuksesan pada kampanye ini, beberapa hal yang harus diraih adalah sikap positif pengguna media sosial terhadap kampanye dan intensi yang tinggi untuk memberikan rekomendasi (word of mouth) kepada orang lain. Penelitian ini dilakukan untuk menganalisis motivasi pengguna apa saja yang memengaruhi sikap pengguna media sosial terhadap kampanye sosial (stop illegal fishing) di media sosial. Selain itu menganalisis sikap pengguna berpengaruh pada intensi pengguna untuk melakukan WOM. Metode yang digunakan untuk menjawab tujuan adalah dengan metode  Partial Least Square. Hasil penelitian menunjukkan motivasi pengguna untuk menggunakan media sosial dan terhadap pesan kampanye terbukti secara signifikan berpengaruh positif pada sikap pengguna terhadap kampanye sosial di media sosial. Selain itu peningkatan intensi untuk memberi WOM dipengaruhi secara positif oleh sikap pengguna media sosial.  Terdapat perbedaan motivasi yang memengaruhi sikap pengguna media sosial terhadap kampanye pada dua kategori kelompok, yaitu pengguna media sosial yang belum pernah (151 sampel) dan pengguna media sosial yang pernah melihat kampanye Stop Illegal Fishing di media sosial.       Kata kunci: motivasi, sikap, word of mouth, pengalaman pengguna, teori uses & gratification, kampanye digital, kampanye sosial, stop illegal fishing